2014
DOI: 10.5897/ajpp2014.4000
|View full text |Cite
|
Sign up to set email alerts
|

Availability of essential medicines in public hospitals: A study of selected public hospitals in Nakuru County, Kenya

Abstract: The aim of this study was to confirm the level of availability of essential medicines in public hospitals in Kenya and the factors leading to this. A cross-section approach was adopted for the research which was conducted across several public hospitals in Nakuru County. Data was collected using questionnaires as the main tool. The findings revealed that majority of the essential medicines that include common antibiotics, common analgesics, antihypertensives, emergency drugs and pediatric formulations were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…The barriers related to other stakeholders’ knowledge and skills reported include inadequate training on rational use of medicines 90, 91 , inadequate knowledge of health commodities and financial reports amongst health facility and governing committee members 92 , unequal access to information on medical products to all stakeholders 88 , and variation in the knowledge of child-appropriate dosage formulations among stakeholders 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The barriers related to other stakeholders’ knowledge and skills reported include inadequate training on rational use of medicines 90, 91 , inadequate knowledge of health commodities and financial reports amongst health facility and governing committee members 92 , unequal access to information on medical products to all stakeholders 88 , and variation in the knowledge of child-appropriate dosage formulations among stakeholders 46 .…”
Section: Resultsmentioning
confidence: 99%
“…This compares well with a study by Mwathi and Osuga which found out that there was a significant relationship between funding and availability of medicines. Inadequate funding was the most strongly cited (57.9%) factor that caused unavailability of essential medicines in public hospitals [17] . Funding is very necessary in acquiring any property and therefore lack of it means acquisition of the said property will not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent theme in this domain was the stakeholder's knowledge and skills to facilitate the implementation of EML. The common barriers reported include inadequate training on rational use of medicines [135,136], inadequate understanding of health commodities and financial reports amongst health facility and governing committee members [89], unequal access to information on medical products to all stakeholders [98], and variation in the knowledge of child-appropriate dosage formulations among stakeholders [50].…”
Section: Plos Global Public Healthmentioning
confidence: 99%